Transition to a sustainable energy production and consumption model – mapping the patterns of success - Popescu, Maria-Floriana; Constantin, Marius; Chiripuci, Bogdan Cristian (Journal of Business Economics and Management, 2022)
This research paper fills a literature gap by tapping into Europe’s Just Transition to green energy production and consumption models and introduces empirically derived trends. The mix of analysed variables was targeted at sustainable energy transformation models according to complementary economic research areas. Based on the clustered heat maps method, double dendrograms were constructed to identify socioeconomic and environmental patterns that characterize highly economic-efficient and sustainable transition patterns from the standard energy production and consumption model to the environmental-friendly and cost-efficient model in the European area. Results show that Austria, Denmark, Norway, Ireland, and Luxembourg followed the patterns of highly economically performant European countries that turned energy and resource productivity in their favour based on multiple factors: recycling, R&D, innovation, digitization. The opposite was observed in the case of many South-Eastern European countries. Robustness checks were performed based on the linear discriminant analysis methodology and results confirmed that Northern European countries lead the change to a more sustainable future. In this context, this research brings empirical results for decision-makers and aims to facilitate a better understanding for adapting policies according to national needs, as well as to the patterns of success identified in the case of European leaders.First published online 15 June 2022